1996
DOI: 10.5014/ajot.50.1.47
|View full text |Cite
|
Sign up to set email alerts
|

A Pet Therapy Intervention With Geriatric Psychiatry Inpatients

Abstract: This pilot study demonstrates the need for further research on animal-assisted interventions with hospitalized elderly persons. Differential improvement in women with dementia also requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 15 publications
2
53
0
5
Order By: Relevance
“…Walsh, Mertin, Verlander, and Pollard (1995) noted that the studies on animals have shown that the beneficial effects are usually transient, tending to diminish when the animal is removed. Another study found that the level of function of elderly residents did not improve when a pet intervention group was compared to an exercise group (Zisselman, Rovner, Shmuely, & Ferrie, 1995).…”
Section: Motivation and Performancementioning
confidence: 98%
“…Walsh, Mertin, Verlander, and Pollard (1995) noted that the studies on animals have shown that the beneficial effects are usually transient, tending to diminish when the animal is removed. Another study found that the level of function of elderly residents did not improve when a pet intervention group was compared to an exercise group (Zisselman, Rovner, Shmuely, & Ferrie, 1995).…”
Section: Motivation and Performancementioning
confidence: 98%
“…Estudos mostram benefícios tangíveis da interação dos animais com grupos de pacientes geriátricos [6,11]. No decorrer do desenvolvimento do projeto, foi observada uma comunicação positiva entre os idosos e a equipe do projeto durante a visita dos animais (Figuras 4 e 5).…”
Section: R E S U Lta D O S E D I S C U S S õ E Sunclassified
“…Ramos [11] indica que a velhice representa a fase da vida onde há uma alta incidência de doenças crônicas não transmissíveis, limitações físicas e perdas refletidas em isolamento social, declínio sensorial e cognitivo.…”
Section: Introductionunclassified
“…Stroking animals can have calming effects [53]. A study of 58 gerontopsychiatric patients (most of whom suffered from depression or dementia) who were divided randomly between a group with pets and a comparison group, showed that after a 5-day intervention built principally around contact with dogs there were no changes within the pet group nor significant differences between the two groups with respect to irritability or withdrawn behaviour [54]. The effects of pet therapy on challenging behaviour in the particular case of dementia patients have yet to be examined.…”
Section: General Therapy Principlesmentioning
confidence: 99%